Dampak Perceraian Orangtua Terhadap Pendidikan Spiritual Anak di Desa Karduluk Tahun 2020 - Khoiriyah (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2021)
Ideally, the education of children in the family is played by the father and mother as the primary and first education. However, the situation becomes lame when a divorce occurs in a family.The father or mother will be the sole actor in the child's education in their daily life in the family environment. This study aims to determine the spiritual education process of children in divorce and the impact of parental divorce on children's spiritual education. The method in this study uses a qualitative approach with case studies. The data sources in this study were obtained by parents and children. The data collection techniques used were interviews, observation and documentation. The results of this study were obtained using the spiritual education process of children in divorced families by submitting children's education to the boarding school, most parents, to improve the morals of worship and remind children about daily activities to improve faith practiced by mankind and provide advice to children. a form of mandate, a behavior that must be carried out by all parents in order to choose peers who can lead to kindness, a group of good playmates, good for adolescent development, the impact of parental divorce on children's spiritual education is difficult to regulate, insensitive to the surrounding environment occurs during adolescence marked by desire to get rid of the reluctance to work, feel bored, self-control anxiety, emotional, lack of self-confidence which causes children to drop out of school due to environmental factors, promiscuity and lead to disappointment, stress, anxiety, trauma so that a this situation is much different from a whole family whose parents are strict in maturing their children, while parents tend to be self-limiting, aggressive, easily influenced, and indifferent to their parents.